Evaluation of Two Implants for Steers on Early-Intensively Grazed Tallgrass Native Range - J. K. Farney; M. E. Corrigan (Kansas Agricultural Experiment Station Research Reports, 2019)
Objective:To evaluate the effect of two implants that have different lengths of effective use on stocker cattle gains within an intensive early double-stocked native tallgrass prairie grazing system. Study Description:Stocker steers (n = 281) were implanted with Revalor-G (Merck Animal Health, Madison, NJ) or Synovex One Grass (Zoetis, Inc., Kalamazoo, MI) and grazed on tallgrass native range for 90 days during the summer. The steers were individually weighed, after an overnight shrink, on the day of implanting, at midpoint of grazing, and the end of the grazing period. Total gains and average daily gain were evaluated. The Bottom Line:Cattle performance was similar regardless of hormone amount and coating technology for these implants when used during a short duration grazing period with stocker steers.
Keywords: average daily gain; intensive grazing